2018
DOI: 10.1071/an17057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano-selenium and nano-zinc particles during in vitro maturation on the developmental competence of bovine oocytes

Abstract: The objectives of the current study were to evaluate the effects of supplemental nano-selenium (NSe) and nano-zinc oxide (NZn-O) particles during in vitro maturation (IVM) on DNA damage of cumulus cells, glutathione (GSH) concentration in bovine oocytes, subsequent embryo development and re-expansion rate of vitrified warmed blastocysts. The current study was conducted on bovine ovaries obtained from a local abattoir and transported to the laboratory in sterile phosphate buffer saline with antibiotics at 37°C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In parthenogenetic embryo production, the oocyte maturation rate was significantly higher in the CNPs25‐treated group compared to that of the control and other treated groups. These findings are in agreement with the previous study investigating nanoparticle treatment in bovine oocytes, although in addition, we have now determined that there lies a cut‐off whereby higher concentrations of CNPs no longer improve competence, and instead adversely affect the benefits of such treatment (Abdel‐Halim & Helmy, 2018). Furthermore, cleavage and blastocyst development rates were significantly higher in the CNPs25‐treated group, not only compared to the control but also the CNPs50‐treated group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In parthenogenetic embryo production, the oocyte maturation rate was significantly higher in the CNPs25‐treated group compared to that of the control and other treated groups. These findings are in agreement with the previous study investigating nanoparticle treatment in bovine oocytes, although in addition, we have now determined that there lies a cut‐off whereby higher concentrations of CNPs no longer improve competence, and instead adversely affect the benefits of such treatment (Abdel‐Halim & Helmy, 2018). Furthermore, cleavage and blastocyst development rates were significantly higher in the CNPs25‐treated group, not only compared to the control but also the CNPs50‐treated group.…”
Section: Discussionsupporting
confidence: 92%
“…The increased GSH level in the CNPs25‐treated group may be due to the preservation of the structural integrity of cytoplasmic organelles which prevent ROS damage and that facilitate the enzyme systems involved in GSH synthesis. Reflecting similar findings, an increase in GSH was observed following the treatment of nano‐selenium and nano‐zinc oxide in bovine oocytes during IVM (Abdel‐Halim & Helmy, 2018).…”
Section: Discussionmentioning
confidence: 54%
“…Bovine COCs matured in vitro in the presence of copper and ZnO nanoparticles had increased intracellular glutathione content of cumulus cells and consequently in vitro improved embryo development (Abdel‐Halim, Moselhy, et al, 2018). The presence of nano‐selenium and nano‐ZnO nanoparticles during in vitro maturation of bovine COCs also increased both intracellular glutathione concentration and DNA integrity of cumulus cells (Abdel‐Halim & Helmy, 2018). Increased levels of glutathione in cultured cells are very important to control oxidative stress (Adeoye et al, 2018).…”
Section: Effects Of Nanoparticles On Cumulus‐oocyte Complexes Matured In Vitromentioning
confidence: 99%
“…Various studies reported that nanoparticles have been used to improve the selection of sperm, semen sexing, and cryopreservation (Bisla et al, 2020; Domínguez et al, 2018; Isaac et al, 2017), as well as to improve survival of preantral follicles (Karime et al, 2020) and COC maturation (Abdel‐Halim & Helmy, 2018). These observations indicate the potential of using nanomaterials to improve ART and emphasize the importance of knowing the recent advances about these smart nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that dietary Se supplementation enhanced reproductive function in mice, sheep and cattle [94,95] and also brought about the improvement in post-thaw spermatozoa quality [66]. Lack of Se has been related to reproductive problems and diminished spermatozoa quality in mice, pigs, sheep and cattle [96], but excessive Se intake also has been connected to an impaired spermatozoa quality [97].…”
Section: Production Of Ros During Cryopreservationmentioning
confidence: 99%